Tissue-Based Thrombolysis for Wake-Up Stroke With Basilar Artery Occlusion: A Case Report. (January 2023) - Janocko, Nicholas J.; Seitz, Alison; Tsiouris, A. J.; Lappin, Richard I.; Navi, Babak B.
Stroke from basilar artery occlusion is associated with a poor natural history with high rates of death and disability. Intravenous thrombolysis administered within 4.5 hours of last known well time improves the odds of a good neurological outcome after ischemic stroke, including in patients with basilar artery occlusion. Thrombectomy for basilar artery occlusion has had mixed outcomes. The WAKE-UP randomized clinical trial demonstrated that administration of intravenous thrombolysis can benefit select patients with wake-up strokes whose brain MRI shows restricted diffusion but no accompanying T2 FLAIR change. We report a case of a wake-up acute ischemic stroke presenting with acute vertigo followed by progressive brainstem dysfunction from a basilar artery occlusion. The patient was successfully treated with intravenous thrombolysis beyond 4.5 hours of last known well and symptom discovery time according to an MRI tissue-based approach resulting in partial recanalization of her basilar artery and recovery to near normal. This case suggests that hyperacute MRI can serve as a tissue clock to select patients with wake-up stroke for acute reperfusion therapy even if they do not meet standard trial inclusion criteria, including patients with basilar artery occlusion.